Opportunistic infections of the retina in patients with aquaporin-4 antibody disease. - George, J; Leite, M; Kitley, J; Jones, N; Cortes, N; Donati, M; Matthews, B; Calladine, D; Hillier, C; Yusuf, I; Munneke, R; Patel, C; et al. (American Medical Association, 2014)
IMPORTANCE: Patients with neuromyelitis optica who have aquaporin-4 antibodies are being identified and receiving immunosuppressant treatment earlier and more aggressively as a result of increasing awareness of the importance of preventing relapses responsible for the high morbidity and mortality associated with the disease. To our knowledge, opportunistic retinal infection in patients with aquaporin-4 antibodies who are receiving immunosuppressants has not been reported to date. OBSERVATIONS: We describe 2 patients with aquaporin-4 antibodies who were receiving conventional doses of first-line immunosuppressive therapy. Both patients presented with vision loss that was initially thought to be optic neuritis attacks. The subsequent diagnoses were ocular toxoplasmosis and cytomegalovirus retinitis. CONCLUSIONS AND RELEVANCE: Retinal opportunistic infections can occur in patients with aquaporin-4 antibodies who are receiving relatively low levels of immunosuppression, may mimic optic neuritis, and are a potentially reversible cause of vision loss when treated promptly.